1995
DOI: 10.1111/j.1346-8138.1995.tb03415.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins Specific to Mosquito Salivary Gland Proteins in the Sera of Persons with Common or Hypersensitive Reactions to Mosquito Bites

Abstract: Using the immunoblot technique, we analyzed the quality and quantity of IgG, IgG4, and IgE specific to mosquito salivary gland (hereafter abbreviate as SG) components of Aedes albopictus in the sera of volunteers with common reactions and of 3 patients with severe reactions. In the volunteers with delayed reactions only or with both delayed and immediate reactions, IgG against SG components of A. albopictus formed several faint or moderately stained bands. Those with immediate reactions showed several intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
(13 reference statements)
2
16
0
1
Order By: Relevance
“…Prior studies investigating host humoral responses against ectoparasite saliva has revealed an important role for IgG, with major contribution of isotype IgG1, IgM, and IgE [4,[37][38][39][40]. Our group has also investigated humoral response against sand fly saliva in a murine model [25], and in children living on an endemic area of visceral leishmaniasis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies investigating host humoral responses against ectoparasite saliva has revealed an important role for IgG, with major contribution of isotype IgG1, IgM, and IgE [4,[37][38][39][40]. Our group has also investigated humoral response against sand fly saliva in a murine model [25], and in children living on an endemic area of visceral leishmaniasis [18].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 They may indicate a classic type I hypersensitivity 20 and are often associated with IgG4 antibodies. 18 To test whether the presence of IgG4 antibodies against P. papatasi saliva antibodies was related or not to an allergic reaction to the saliva, the production of IgE antibodies against P. papatasi saliva was investigated and the correlation between IgE and IgG4 antibodies analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding mammalian response to insect saliva is of utmost importance in several ways. Besides being related to allergy (1,2), insect saliva is known to facilitate parasite survival (3)(4)(5). In mice, saliva from Lutzomyia longipalpis or Phlebotomus papatasi leads to larger Leishmania major-associated lesions than those resulting from the parasite alone (6).…”
mentioning
confidence: 99%